Eye movement parameters for performance evaluation in projection-based stereoscopic display - Chiuhsiang Joe Lin; Yogi Tri Prasetyo; Retno Widyaningrum (Bern Open Publishing, 2018)
The current study applied Structural Equation Modeling (SEM) to analyze the relationship among index of difficulty (ID) and parallax on eye movement time (EMT), fixation duration (FD), time to first fixation (TFF), number of fixation (NF), and eye gaze accuracy (AC) simultaneously. EMT, FD, TFF, NF, and AC were measured in the projection-based stereoscopic display by utilizing Tobii eye tracker system. SEM proved that ID had significant direct effects on EMT, NF, and FD also a significant indirect effect on NF. However, ID was found not a strong predictor for AC. SEM also proved that parallax had significant direct effects on EMT, NF, FD, TFF, and AC. Apart from the direct effect, parallax also had significant indirect effects on NF and AC. Regarding the interrelationship among dependent variables, there were significant indirect effects of FD and TFF on AC. Our results concluded that higher AC was achieved by lowering parallax (at the screen), longer EMT, higher NF, longer FD, and longer TF,